PENGARUH BUDAYA PERUSAHAAN DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT BANK JABAR BANTEN CABANG SERANG - Nurhayati, Kartika; Pradhanawati, Ari; Wijayanto, Andi (Jurnal Ilmu Administrasi Bisnis, 2014)
Labor productivity is affected by several factors, such as strong corporate culture and a good working environment. This study aims to identify and explain the influence of culture and work environment on employee productivity PT Bank Jabar Banten (BJB) branch of Serang. This type of research is explanatory research. Techniques of data collection using interviews, questionnaires and observation. The conclusion from this study is that there is influence between corporate culture and work environment on employee productivity. Based on the conclusion that the company needs to provide oversight of corporate culture in order to better control and there needs to be comfortable working environment for the employees so as to improve the productivity of previous work.